PENGARUH BEBAN KERJA DAN KONFLIK INTERPERSONAL TERHADAP STRES KERJA PEGAWAI DI INSTALASI GIZI RSUD ANDI DJEMMA MASAMBA - Pratiwi, Nayla Jingga; Haedar; Hasbi, Andi Rizkiyah (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aims to analyze the impact of workload and interpersonal conflict on work-related stress among employees in the Nutrition Installation at RSUD Andi Djemma Masamba. The method used is a quantitative approach with statistical analysis utilizing multiple linear regression. Data collection techniques involved distributing questionnaires to all employees in the Nutrition Installation, totaling thirty-one individuals. The results indicate that workload has a significant effect on work-related stress, as does interpersonal conflict, which exacerbates the situation. Statistical tests reveal that the combined influence of these two variables on employees' stress levels is also significant. Overall, the findings demonstrate that both workload and interpersonal conflict substantially contribute to the level of stress experienced by employees. This research highlights the importance of hospital management in effectively managing workload and creating a harmonious work environment. By implementing appropriate measures, such as fair task distribution and strengthening communication among employees, it is hoped that work-related stress can be minimized, ultimately improving the quality of care provided to patients.